Implementasi Pengabdian Masyarakat Berbasis Kesehatan Dalam Upaya Pencegahan Penyakit Covid 19 di Desa Bedulu Gianyar Bali - Ika Setya Purwanti; Ni Luh Putu Devhy; Diah Prihatiningsih; Ni Wayan Desi Bintari; A.A Gde Oka Widana5 Oka Widana (Jurnal Pengabdian UNDIKMA, 2020)
This service activity aims to increase citizen awareness of the importance of using masks and washing hands using soap and running water for at least 20 seconds.. This community service activity was held in Bedulu Village, Gianyar Bali in April 2020. The method of activity carried out is by distributing masks, vitamins, soap, disinfectant liquid and also leaflets/posters on how to prevent COVID 19. This poster will be posted in several strategic places so that it can be seen directly by the public. Participants in this community service activity were carried out by a team of STIKes WIra Medika Bali lectures and also assisted by students. As a result of this community service activity, the community knows how to wash their hands, how to use masks and can spray disinfectans in their home environment.